Role of Dlg5/lp-dlg, a Membrane-Associated Guanylate Kinase Family Protein, in Epithelial-Mesenchymal Transition in LLc-PK1 Renal Epithelial Cells - Sezaki, Takuhito; Inada, Kohki; Sogabe, Takayuki; Kakuda, Kumiyo; Tomiyama, Lucia; Matsuno, Yohsuke; Ichikawa, Takafumi; Matsuo, Michinori; Ueda, Kazumitsu; Kioka, Noriyuki (PLOS ONE, 2012)
Discs large homolog 5 (Dlg5) is a member of the membrane-associated guanylate kinase adaptor family of proteins, some of which are involved in the regulation of epithelial-to-mesenchymal transition (EMT). Dlg5 has been described as a susceptibility gene for Crohn's disease; however, the physiological function of Dlg5 is unknown. We show here that transforming growth factor-β (TGF-β)-induced EMT suppresses Dlg5 expression in LLc-PK1 cells. Depletion of Dlg5 expression by knockdown promoted the expression of the mesenchymal marker proteins, fibronectin and α-smooth muscle actin, and suppressed the expression of E-cadherin. In addition, activation of JNK and p38, which are stimulated by TGF-β, was enhanced by Dlg5 depletion. Furthermore, inhibition of the TGF-β receptor suppressed the effects of Dlg5 depletion. These observations suggest that Dlg5 is involved in the regulation of TGF-βreceptor-dependent signals and EMT.